Human protein interaction networks across tissues and diseases - Yeger-Lotem, Esti; Sharan, Roded (Frontiers in Genetics, 2015)
Protein interaction networks are an important framework for studying protein function, cellular processes, and genotype-to-phenotype relationships. While our view of the human interactome is constantly expanding, less is known about networks that form in biologically important contexts such as within distinct tissues or in disease conditions. Here we review efforts to characterize these networks and to harness them to gain insights into the molecular mechanisms underlying human disease.